2022
DOI: 10.1155/2022/1574774
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of “Internet+” Based Cardiac Rehabilitation on Prognosis of Patients with Coronary Heart Disease: A Meta-Analysis

Abstract: Objective. Meta-analysis was used to systematically evaluate the impact of Internet-based cardiac rehabilitation on the health of patients with coronary heart disease. Methods. Randomized controlled trial study (RCTs) of the effects of Internet-based cardiac rehabilitation on cardiovascular risk factors, motor function and psychological status in patients with coronary heart disease has been systematically studied. Results. A total of 13 articles were included. Meta-analysis showed that internet-based cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The intervention-rehabilitation outcomes mapping which incorporated data from 51 SRs reported rehabilitation outcomes was shown in Figure 5 . 27 , 35 - 48 , 50 - 58 , 60 - 62 , 65 - 70 , 72 - 75 , 77 - 89 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…The intervention-rehabilitation outcomes mapping which incorporated data from 51 SRs reported rehabilitation outcomes was shown in Figure 5 . 27 , 35 - 48 , 50 - 58 , 60 - 62 , 65 - 70 , 72 - 75 , 77 - 89 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%